DIPLOMASI INDONESIA DALAM MENINGKATKAN JUMLAH KUNJUNGAN WISATAWAN KOREA SELATAN KE INDONESIA - Ni Luh Putu Dessi Chandra Astari; Machya Astuti Dewi (Jurnal Studi Diplomasi dan Keamanan, 2017)
This research discusses about the efforts of Indonesian diplomacy in increasing the number of South Korean tourist’s visit to Indonesia. South Korea is the main target of Indonesian tourism because of its important position as a partner in cooperation including tourism. South Korea is one of the potential targets that can provide a share of significant foreign tourist arrivals. South Korea also has a great interest in honeymoon, golf, and leisure package that match with Indonesian market. This research uses the concept of public diplomacy. The method is qualitative method. Data were collected from secondary data, such as books, journals, and websites. The results of this research highlight that the efforts of Indonesian diplomacy to promote Indonesian tourism in South Korea has not been successful yet. The government failed to reach the target of bringing 400 thousand South Korean tourists in 2016.